Depressive symptoms and all-cause mortality among middle-aged and older people in China and associations with chronic diseases - Zhu, Lan; Wang, Yixi; Li, Jiaqi; Zhou, Huan; Li, Ningxiu; Wang, Yuanyuan (Frontiers in Public Health, 2024)
Introduction: It remains unclear whether depressive symptoms are associated with increased all-cause mortality and to what extent depressive symptoms are associated with chronic disease and all-cause mortality. The study aims to explore the relationship between depressive symptoms and all-cause mortality, and how depressive symptoms may in turn affect all-cause mortality among Chinese middle-aged and older people through chronic diseases. Methods: Data were collected from the China Health and Retirement Longitudinal Study (CHARLS). This cohort study involved 13,855 individuals from Wave 1 (2011) to Wave 6 (2020) of the CHARLS, which is a nationally representative survey that collects information from Chinese residents ages 45 and older to explore intrinsic mechanisms between depressive symptoms and all-cause mortality. The Centre for Epidemiological Studies Depression Scale (CES-D-10) was validated through the CHARLS. Covariates included socioeconomic variables, living habits, and self-reported history of chronic diseases. Kaplan-Meier curves depicted mortality rates by depressive symptom levels, with Cox proportional hazards regression models estimating the hazard ratios (HRs) of all-cause mortality. Results: Of 13,855 participants included, the median (Q1, Q3) age was 58.00 (51.00, 63.00) years. Adjusted for all covariates, middle-aged and older adults with depressive symptoms had a higher all-cause mortality rate (HR = 1.20 [95% CI, 1.09-1.33]). An increased rate was observed for 55-64 years old (HR =1.23 [95% CI, 1.03-1.47]) and more than 65 years old (HR=1.32 [95% CI, 1.18-1.49]), agricultural hukou (HR=1.44, [95% CI, 1.30-1.59) and non-agricultural workload (HR = 1.81 [95% CI, 1.61-2.03]). Depressive symptoms increase the risks of all-cause mortality among patients with hypertension (HR = 1.19 [95% CI, 1.00-1.40]), diabetes (HR = 1.41[95% CI, 1.02-1.95]) and arthritis (HR = 1.29 [95% CI, 1.09-1.51]) Conclusion: Depressive symptoms raise all-cause mortality risk, particularly in those aged 55 and above, rural household registration (agricultural hukou), and non-agricultural workers, and middle-aged and older people with hypertension, diabetes, and arthritis. Our findings, through the longitudinal data collected in this study, offer valuable insights for interventions targeting depression, such as early detection, integrated chronic disease care management, healthy lifestyles, and community support for depressive symptoms may help to reduce mortality in middle-aged and older people.